Evaluation of sheets of irrigation for rice cultivation - Loqui, Aldo; Díaz Castillo, Aslam; Zambrano, Marcelo (Revista Universidad de Guayaquil, 2018)
Aims of the study determine the behavior of productive indicators of rice, with the use of different irrigation depths. The work was carried out in La Victoria, saltpeter, Guayas, Ecuador. The variety of rice INIAP-12, in pitches of 80 m2, with irrigation every 15 days and 90 kg of urea was used / has (15-30 days). Design of blocks at random, three groups (5, 10 and 15 cm of irrigation), 3 replicas/group and 12 plots. Were compared: children/plant/m2; height of plants; plants with fallen growth; panicle/m2; filled seeds; weight of 1000 seeds/m2; production of seeds with 14% moisture and economic viability. As a result was a greater number of children per plant (424 ±42 children/m2); panicles (413.50 ±12/m2); filled seeds (92 7%); higher seed weight (29.75 ±5 g/1000 seeds/m2); more seeds by has (84.15 7 kg / has); lower plant height (99.25 ±2 cm); plants with growth fallen (10 ±2%); (10 ±2%); cost (2.94) benefit and cost per kg ( 0.06) were obtained with 5 cm of irrigation. Irrigation of 15 cm produced the worst production indicators and less economic utility. As conclusions emphasize the best productive indicators of rice obtained with 5 cm of irrigation. The feasibility was favorable in all cases, but the best economic results were obtained in irrigation of 5 cm. He is not recommended to hold a flood of 15 cm of irrigation in rice cultivation.